Toleransi Beragama Dalam Hadis Nabi - Nasir, Mohaammad; Qomariya, Nurul (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2021)
Hadith has taught to build a harmony in social life, which makes Islam a rahmatan lil alamin. Which the Messenger of Allah has practiced and also in one of his words, namely the hadith and even the Islamic empires in conquering peacefully. One of them includes religious tolerance in order to respect, respect, protect, and provide freedom of worship. in inter-religious matters except in terms of theology (belief). With one goal, namely, to achieve unity and unity in national and state relations which will later have an impact on the order of people's lives and also what the prophet aspires to. To be informed that Islam is a religion of peace, in which the Messenger of Allah is the bearer of the banner of truth.